DESIGN OF TRAILER STRUCTURE FOR 12 TON PAYLOAD USING ADVANCED LIGHTWEIGHT MATERIAL FOR WEIGHT REDUCTION - Vyom Bhushan; Sanjay D. Yadav (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Automotive structure is a vital component of every vehicle. It gives strength to the vehicle. Generally, all structures of truck-trailers which are commercial in nature have heavy weight because of that they have high fuel consumption and high emission which spoils the environment. In this research, an effort has been tried for selecting advanced lightweight material with high strength and low density for weight reduction. Finally, considerable weight reduction of 73.6% has been observed in the structure using advanced lightweight material. In addition, the fuel consumption and emissions of the vehicle decrease, which results to prevention of environment from pollution due to vehicles.